Complete microbial synthesis of crocetin and crocins from glycerol in Escherichia coli - Lee, Jun Ho; Lee, Seong Rae; Lee, Sang Yup; Lee, Pyung Cheon (Microbial Cell Factories, 2024)
Background: Crocin, a glycosylated apocarotenoid pigment predominantly found in saffron, has garnered significant interest in the field of biotechnology for its bioactive properties. Traditional production of crocins and their aglycone, crocetin, typically involves extraction from crocin-producing plants. This study aimed to develop an alternative biosynthetic method for these compounds by engineering the metabolic pathways of zeaxanthin, crocetin, and crocin in Escherichia coli strains. Results: Employing a series of genetic modifications and the strategic overexpression of key enzymes, we successfully established a complete microbial pathway for synthesizing crocetin and four glycosylated derivatives of crocetin, utilizing glycerol as the primary carbon source. The overexpression of zeaxanthin cleavage dioxygenase and a novel variant of crocetin dialdehyde dehydrogenase resulted in a notable yield of crocetin (34.77 ± 1.03 mg/L). Further optimization involved the overexpression of new types of crocetin and crocin-2 glycosyltransferases, facilitating the production of crocin-1 (6.29 ± 0.19 mg/L), crocin-2 (5.29 ± 0.24 mg/L), crocin-3 (1.48 ± 0.10 mg/L), and crocin-4 (2.72 ± 0.13 mg/L). Conclusions: This investigation introduces a pioneering and integrated microbial synthesis method for generating crocin and its derivatives, employing glycerol as a sustainable carbon feedstock. The substantial yields achieved highlight the commercial potential of microbial-derived crocins as an eco-friendly alternative to plant extraction methods. The development of these microbial processes not only broadens the scope for crocin production but also suggests significant implications for the exploitation of bioengineered compounds in pharmaceutical and food industries.
Keywords: Carbon; Escherichia coli; Glycerol; Zeaxanthins; Crocetin; Crocin; Metabolic engineering; Saffron